Application of advanced encryption standard in the computer or handheld online year-round registration system - Jomar L. Calpito; Paul L. Olanday; Alain C. Gallarde (Institute of Advanced Engineering and Science, 2022)
With various severe security threats for web applications, ensuring security on the database layer itself is imperative. Hence, this study aims to protect data saved on the computer or handheld online year-round (CHOY) registration system using the advanced encryption standard (AES) to strengthen data security within the app so that even potential attackers gain access to the app's database; they cannot obtain valuable information because it is scrambled and unreadable. The proponents based the study's conceptual framework on the symmetric and asymmetric key algorithms and procedures manual on enrollment of Southern Isabela College of arts and trades (SICAT) and ISO 25010. The study consists of three elements: developing the CHOY web app imbued with AES, testing it in terms of online registration and spam prevention, and evaluating it using the ISO 25010 in terms of compatibility, reliability, and security. The evaluation results show that implementing the AES in the CHOY web app meets the ISO 25010 criteria mentioned above.